Era of Disruptions: Entrepreneurs’ Experiences and Challenges on Business Sustainability in Nigeria - Nkiruka, Ezeanokwasa Francisca; Chinelo, Nwagbala Stella; Raphael, Nwachukwu; Nwadiogo, Oranusi Ifeanyichukwu; Ejike, Ani Anthony (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Entrepreneurship disruptions have become a pervasive and transformative force in today's global business landscape. These disruptions are characterized by the rapid and often unpredictable changes that impact the way entrepreneurs conceive, launch, and operate businesses. In the modern era, the rapid pace of technological advancement and the rise of disruptive innovations have presented a significant challenge for entrepreneurs and established businesses alike. As entrepreneurs strive to identify and leverage disruptive opportunities, they face complex issues related to market dynamics, economic instability resource allocation, and competitive pressures. Moreover, the ever-accelerating rate of disruption necessitates a deeper understanding of how entrepreneurs can effectively navigate these challenges while staying innovative and sustainable. This study seeks to identify and analyse the experiences and challenges faced by businesses in their pursuit of sustainability during this disruptive era. Data were generated via the internet, newspapers, newsletters, libraries and other documented materials pertinent to the study. Findings revealed that there is a positive relationship between entrepreneurship disruptions and business sustainability in Nigeria. To fully harness disruptive entrepreneurship and achieve sustainability, regulatory reforms, technological advancements, changing consumer behaviour, infrastructure development, and increased access to funding are crucial. Consequently, to address these challenges and promote sustainability, it is imperative to conduct a comprehensive analysis of the experiences and challenges faced by businesses and individuals in the disruption era, businesses in Nigeria need to adopt innovative solutions, and collaborate with relevant stakeholders while keeping a close eye on regulatory changes and global trends.